Assessing the Role of State and Local Public Health in Outreach and Enrollment for Expanded Coverage A Case Study on Tacoma-Pierce County, Washington - Bharmal, Nazleen (RAND Corporation, 2016)
Part of a series on innovative models and best practices for leveraging local health departments' involvement in Patient Protection and Affordable Care Act outreach and enrollment, this report describes a case study on Tacoma-Pierce County, Washington, that captures nuanced differences in how health departments support these efforts, identifies facilitators and barriers to these approaches, and develop lessons learned from these activities.